1991
DOI: 10.21273/hortsci.26.10.1341
|View full text |Cite
|
Sign up to set email alerts
|

`Willamette' Hazelnut

Abstract: Additional index words. nut breeding, filbert, Corylus avellana, blanched kernels, disease resistance 'Willamette' hazelnut (Corylus avellana L.) was released in 1990 for the blanched kernel market. Compared with 'Barcelona', the leading cultivar in Oregon, 'Willamette' yields 50% more marketable kernels. Nuts have thinner, more attractive shells with fewer defects. The pellicle is removed easily with dry heat, and the resulting white kernels are of excellent quality for use in pastries and confections. 'Willa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…The I 2 calculated values, were, for all of them, higher than 94%. 'Willamette' also scored a high value, according to Mehlenbacher et al (1991), but in disagreement with observations of Ciarniello et al (2014). This is an interesting trait for industrial processing (Di Matteo et al, 2012).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The I 2 calculated values, were, for all of them, higher than 94%. 'Willamette' also scored a high value, according to Mehlenbacher et al (1991), but in disagreement with observations of Ciarniello et al (2014). This is an interesting trait for industrial processing (Di Matteo et al, 2012).…”
Section: Resultsmentioning
confidence: 61%
“…Trees received fertilizers recommended for this species (Tous et al, 1994), and drip irrigation was calculated each year according the methodology proposed by Allen et al (1998). Eleven own-rooted cultivars were chosen (Table 1): 'Clon La Mas o', 'Negret N-9' [a clonal IRTA selection (Rovira et al, 2006)], 'Negret Primerenc', and 'Pauetet' from the Tarragona area in Spain (Tasias, 1975); 'San Giovanni', 'Tonda di Giffoni', 'Tonda Romana' (Manzo and Tamponi, 1982), and 'Tonda Italiana' from Italy (this last one, an IRTA selection from Italian material); and 'Clark', 'Lewis', and 'Willamette' from the hazelnut breeding program at OSU (Mehlenbacher et al, 1991(Mehlenbacher et al, , 2000.…”
Section: Methodsmentioning
confidence: 99%
“…'Barcelona' is the leading cultivar in Oregon. 'Gasaway' is a pollinizer and highly resistant to eastern filbert blight (Mehlenbacher et al, 1991b), and 'Willamette' is a new cultivar for the blanched kernel market (Mehlenbacher et al, 1991a). 'Newberg' (USOR 7-71) and 'Dundee' are two new nonsuckering rootstocks, selected from open-pollinated C. colurna L. seed.…”
Section: Methodsmentioning
confidence: 99%
“…The EFB-resistant seedling of 'Willamette' strongly suggests a pollen donor transmitting genes for resistance. 'Willamette' was developed in the USA (Mehlenbacher et al, 1991b) and expresses moderate tolerance to EFB in Oregon, but under the high disease pressure (and/or diversity of A. anomala isolates) found in New Jersey, trees of the cultivar showed a high level of susceptibility (Molnar, data not shown). A number of the other seed-parents in this study that yielded resistant seedlings were also previously shown to be susceptible to EFB in Oregon (Table 1), which further supports the premise of an unknown pollen donor contributing genes for resistance.…”
Section: Resultsmentioning
confidence: 99%
“…b Designates cultivars tested at Oregon State University that were shown to be susceptible to EFB (Lunde et al, 2000;Sathuvalli et al, 2010). Note that 'Wilamette' and 'Lewis' were both tolerant of EFB in Oregon (Mehlenbacher et al, 1991b but were found to be highly susceptible in New Jersey (Molnar, unpublished). c Azj designates cultivars originating from Azerbaijan (column 3) or collection sites in Azerbaijan (column 4).…”
Section: Greenhouse Inoculationsmentioning
confidence: 99%